Note—Comments on “Single Cycle Continuous Review Policies for Arborescent Production/Inventory Systems” - Muckstadt, John A.; Singer, Howard M. (Management Science, 1978)
In the paper by Graves and Schwarz [Graves, Stephen C., Leroy B. Schwarz. 1977. Single cycle continuous review policies for arborescent production/inventory systems. Management Sci. 23 (5, January) 529–540.], we observed an error in their discussion of optimal policies for the one warehouse-m retailer system. Specifically, Theorem 1, which states that the optimal stationary policy is a single-cycle policy, is incorrect.